Estudo de misturas solo cimento agregado reciclado de telhas cerâmicas para fabricação de blocos para alvenaria - Silva, Blaine Alves da (2015)
This work aimed to study the incorporation of ceramic residues of tiles crushed in the soilcement mixture in the manufacture of hollow blocks, justified by the amount of these wastes generated by the ceramic tile industry, with potential for recycling. This study aimed to determine a molding energy in laboratory compatible with that of the hydraulic presses of the factory. The DNER-ME 258:1994 test method compacted soils miniature equipment Mini-MCV were used , observing that it is possible to mold bodies of proof in laboratory with ASDM apparent specific dry mass compatible with that of the hollow blocks produced in the factory. Four lots of soil-cement hollow blocks were produced, whose tests allowed to choose the most appropriate mixture, the desired value of ASDM and the number of compatible blows. The ASDM of soil-cement bodies and the blocks were compared, and there was compatibility of values. To study mixtures with the RTA Recycled Tile Aggregate the optimization methodology of the volumes of materials was used in order to fill the gaps in the aggregate with compacted soil-cement. Starting from the gap indices of the aggregate containing cement and the pure aggregate the work began with two soil-cement aggregate mixtures. By projection, other mixtures resulted from these, which, after tests, allowed to select the most adequate. Using this one, hollow blocks were manufactured, whose test results met the standard with regard to strength, but not to water absorption. To reduce the absorption, a waterproofing additive, a stabilizer and an Aloe Vera extract were inserted in the mixture, whose bodies of proof tests registered values within the normative limits in 2 cases. Hollow blocks using the most favorable mix amount were produced, whose tests attended the strength requirements, but not the absorption ones. The results obtained indicate the feasibility of the methods, and that RTA can be used for manufacturing hollow blocks, although this depends on the pressing capability of the factory.